Dynamic Characteristics of Near-wall Single Bubble Collapse-induced Shock Waves - W. Han; Y. Xian; R. Li; W. Li; Y. Hao; Y. Chen (Journal of Applied Fluid Mechanics)
Understanding the kinetic behavior at the scale of a single bubble is crucial for understanding cavitation flow properties. In this study, experiments and numerical analysis of shock waves resulting from the crumpling of a solitary adjacent wall vacuole have been conducted. Shock wave characteristics induced by near-wall bubble collapse were investigated using high-speed photography and shadowgraphy techniques. Numerical simulations were conducted of near-wall vacuole collapse-induced shock-wave dynamics using the OpenFOAM cavitatingFoam solver. (1) The shock wave displays an essentially symmetrical distribution. The pressure maxima diminished along the sagittal diameter. The intensity of the second shock wave generated near the wall was decreased by approximately 21.2% compared to the initial shock wave. The simulated wave speeds exhibit a high level of concordance with the experimental data, and the calculated errors are below 7.9%. (2) The pressure and velocity at which the shock wave propagates in water exhibit a power function and an exponential decay function, respectively, as they travel across distance. And the perturbation profile of the velocity aligned with the direction in which the shock wave propagated. This result indicates that the shock wave acts as a catalyst for the creation of disturbances in the velocity field. (3) Constructing a transformation relation for the wave energy of near-wall vacuole collapse. During its first collapse, the near-wall cavitation bubble lost an average of 85% of its energy. This allowed for the assessment of the erosive impact of cavitation-induced shock waves on rigid surfaces.